Implementation of Sukuk as a Solution for Economic Development in North Sumatra - Pranoto, Jiko; arif, Muhammad; Batubara, Maryam (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to analyze the regulatory system for implementing regional sukuk as a solution for regional economic development in North Sumatra, to analyze the mechanism for implementing regional sukuk as a solution for regional economic development in North Sumatra, and to analyze what factors influence the implementation of regional sukuk as a solution in regional economic development in North Sumatra. The methodology of this research uses a qualitative study approach which emphasizes implementation of regional sukuk (sharia bonds) as a solution for regional economic development in North Sumatra . The data collection techniques used in this research were interviews and documentation. The results of this research are: (1) The regulatory system in implementing regional sukuk as a solution for regional economic development in North Sumatra, including: a) the existence of clear and comprehensive regulations, b) strict supervision, c) sustainability of the regional sukuk program, d) sukuk market development, and e) partnerships. (2) The mechanism for implementing regional sukuk as a solution for regional economic development in North Sumatra can be carried out starting from: a) preparation of regional economic development plans, b) assessment of project feasibility, c) sukuk structure, d) issuance of sukuk, e) use of data sukuk, and f) periodic evaluation and reporting. (3) Factors influencing the implementation of regional sukuk as a solution for regional economic development in North Sumatra can be: a) regulations and policies, b) regional financial capacity, c) availability of investment projects, and d) cooperation between parties.